Characterization of the Trimethylamine N-Oxide Transporter From Pelagibacter Strain HTCC1062 Reveals Its Oligotrophic Niche Adaption - Gao, Chao; Zhang, Nan; He, Xiao-Yan; Wang, Ning; Zhang, Xi-Ying; Wang, Peng; Chen, Xiu-Lan; Zhang, Yu-Zhong; Ding, Jun-Mei; Li, Chun-Yang (Frontiers in Microbiology, 2022)
Trimethylamine N-oxide (TMAO), which was detected at nanomolar concentrations in surface seawaters, is an important carbon, nitrogen and/or energy source for marine bacteria. It can be metabolized by marine bacteria into volatile methylated amines, the second largest source of nitrogen after N2 gas in the oceans. The SAR11 bacteria are the most abundant oligotrophic plankton in the oceans, which represents approximately 30% of the bacterial cells in marine surface waters. Genomic analysis suggested that most SAR11 bacteria possess an ATP-binding cassette transporter TmoXWV that may be responsible for importing TMAO. However, it was still unclear whether SAR11 bacteria can utilize TMAO as the sole nitrogen source and how they import TMAO. Here, our results showed that Pelagibacter strain HTCC1062, a SAR11 bacterium, can grow with TMAO as the sole nitrogen source. TmoXWV from strain HTCC1062 (TmoXWV1062) was verified to be a functional TMAO importer. Furthermore, TmoX1062, the periplasmic substrate binding protein of TmoXWV1062, was shown to have high binding affinities towards TMAO at 4°C (Kd = 920 nM), 10°C (Kd = 500 nM) and 25°C (Kd = 520 nM). The high TMAO binding affinity and strong temperature adaptability of TmoX1062 reveal a possible oligotrophic niche adaptation strategy of strain HTCC1062, which may help it gain a competitive advantage over other bacteria. Structure comparison and mutational analysis indicated that the TMAO binding mechanism of TmoX1062 may have differences from the previously reported mechanism of TmoX of Ruegeria pomeroyi DSS-3. This study provides new insight into TMAO utilization by the widespread SAR11 bacteria.